Patterns of family upbringing and their effects on children’s personality: (An analytical study) - Alneaimi, Naji; Alhalalat , Khalil (Al-Adab Journal, 2024)
The researcher aimed in this study to know the relationship between the patterns of family upbringing and the personality of the children by asking a set of questions that represented the questions of this study and which serve the main objective for which this study was conducted, as the researcher relied in the composition of this study on the literature and previous studies. Which included the variables of his study and other variables that serve the research, and the researcher used the analytical method in his study by describing the studied phenomenon according to different data such as the variables and determinants affecting the process of upbringing. The study, which stated that there is no specific pattern that can be classified as coming first in terms of its prevalence as a pattern followed by the parents, and the study concluded that there is a relationship that varies in the degree of strength between the parental upbringing pattern and the personality of the son, and the study also found that the patterns of upbringing Positivity is linked and positively affects the children’s personality, as well as negative family upbringing patterns affect the son’s personality negatively, and at the conclusion of the study, the researcher recommended the need to intensify research The sober scientific approach and its continuity periodically so that the patterns of family upbringing are dealt with qualitatively, not quantitatively, according to precise variables.